Contextualization and prospective of the cash transfer program -bono de desarrollo humano- in Ecuador. - Meza Cisneros , Josueth Alfonso; Intriago Mendoza, Fernando Rodolfo; Cantos Cruz, Mayra Verónica (SATHIRI, 2022)
Governments around the world in an exercise of social compliance have found in conditional money transfers, known in our country as the human development bond, which provides an economic item that is paid to the beneficiaries through the national banking system. Many citizens are unaware of the operation and the real objective of this type of benefit for the "poor" of our country, in this way it is about contextualizing its creation, objective, and a reflection of the future of this bond.
Keywords: Public Policy; Human Development Bond; Conditional Cash Transfer Program